Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Temporal variability of a soundscape near a mid-oceanic atoll in the northern Indian ocean - Divya Panicker; Kathleen M. Stafford (Progress in Oceanography, 2023)

Northern Indian Ocean blue whale songs recorded off the coast of India - Divya Panicker; Kathleen M. Stafford (Marine Mammal Science, 2021)

Indian Ocean humpback dolphin (Sousa plumbea) estuary‐use patterns in Kochi harbor, India - Divya Panicker; Asad Haris; Dipani Sutaria (Marine Mammal Science, 2018)